Kissinger on Kissinger reflections on diplomacy, grand strategy, and leadership - Lord, Winston (New York All Points Books, 2019)
As National Security Advisor to Richard Nixon, Henry Kissinger transformed America's approach to diplomacy with China, the USSR, Vietnam, and the Middle East, laying the foundations for geopolitics as we know them today.
Includes index.
Keywords: Kissinger, Henry, 1923---Interviews.